The Relationship Between Consumption of Vegetables, Fruits, and Breakfast with the Incidence of Overweight in Students - diyan yunanto setyaji; Valentina Swadhitra Evita Ajeng Avengelista; Rijantono Franciscus Maria (Ikatan Sarjana Gizi Indonesia (ISAGI), 2022)
Overweight is a manifestation of the body due to excess energy intake so that it is stored in more form in the body. During the last ten years there has been an increase in the incidence of overweight and obesity in Indonesia. Students are a group that is vulnerable to experiencing overweight events due to changes in lifestyle that affect eating patterns. Risk factors that can be improved in diet are consumption of vegetables, fruit, and breakfast. This study was conducted to determine the relationship between consumption of vegetables, fruit, and breakfast with the incidence of overweight in students in Sleman Regency. The design of this study was cross-sectional. Data was obtained using a google form questionnaire. Sampling technique with consecutive sampling. The subjects of this study amounted to 251 students. Data analysis used descriptive analysis, Chi-square, Fisher exact, Haenszel Mantel, and multiple logistic regression. The results showed that there was a significant relationship between the consumption of fruit menu types (PR = 0.523 p = 0.043) and the timeliness of breakfast (PR = 0.486 p = 0.047) with the incidence of more overweight in students. There was no significant relationship between consumption of vegetables, types of vegetable menus, amount of fruit, regularity of breakfast, and breakfast components with the incidence of overweight in students (p>0.05). Students who often eat fatty foods and eat breakfast on time have a 2 times greater risk of experiencing more overweight [(95% CI 1.143-4.077) p=0.017]. It can be concluded that there is a significant relationship between the consumption of fruit menus and the timeliness of breakfast with the incidence of more overweight of students. There is no significant relationship between vegetable consumption and the incidence of overweight status of students. Students who often eat fatty foods and eat breakfast on time have a 2.2 times greater risk of experiencing excess overweight.